Dairy Breed Preferences and Breeding Practices Among Smallholder Farmers in Githunguri Sub-county, Kenya - P.A.O, Alaru; A.A, Shitandi; S.M, Mahungu; J.M.K, Muia (African Journal of Education,Science and Technology (AJEST), 2024)
Dairy production plays a critical socio-economic role for most developing countries' populations. The study aimed at assessing dairy breed preferences and breeding practices among smallholder farmers in Githunguri Sub- County, Kenya. The study was conducted through a cross-sectional survey using pretested questionnaires administered to randomly selected 457 smallholder dairy farmers from the eight milk collection routes in the sub-county. Most farmers keep the Friesian breed (93%) and use artificial insemination (A.I.) to serve animals (95.7%). High milk yield was the leading parameter of breed preference. Animal breeding practices significantly differed along the milk collection routes mainly due to variations in age and level of education. Poor animal health was ranked the most critical challenge, followed by inadequate and poor-quality feeds. A large number (69.6%) of farmers do not estimate the live weight of animals. The majority of farmers (44.8%) obtained their replacement breeding stock either from their herd or bought from other farms. Notably, the milk collection route where youths (≤ 35 years of age) actively participated in dairy farming reported the highest number of lactating cows and milk production levels. Tertiary education level (46.1%) and membership in farmer organizations (70.4) had the greatest impact on the proportion of milk produced. Equally, controlled breeding programs guarantee quality breeds and replacement stock for farmers, but poor feeding strategies and animal health challenges hinder genetic progress. These findings demonstrate the need to consider appropriate feeding strategies and animal health management as a prerequisite to improvement in breeding programs. Conversely, there is a need to engage more youth in dairy production and provide technical backstopping to farmers on good agricultural practices for enhanced dairy productivity.